Fabrication of Photonic Crystal Structures on Flexible Organic Light-Emitting Diodes by Using Nano-Imprint and PDMS Mold - Ho Ting-Lin; Hsu Quang-Cherng; Chen Yu-Liang; Liu Bao-Hsin (MATEC Web of Conferences, 2016)
In this paper, nanoimprint lithography was used to create a photonic crystals structure film in organic light-emitting diode (OLED) component, and then compare the efficiency of components whether with nanostructure or not. By using two different kinds of mold, such as silicon mold and PDMS mold, the nano structures in PMMA (molecular weight of 350K) were fabricated. Nanostructures in period of 403.53nm with silicon mold and nano structures in period of 385.64nm with PDMS mold as photonic crystal films were fabricated and were integrated into OLED. In experimental results, the OLED without photonic crystal films (with packing) behaves 193.3cd/m2 for luminous intensity, 3.481cd/A for lightening efficiency (ηL) and 0.781 lm/W for lightening power (ηP) where V is 14V and I is 5.5537mA; the OLED with photonic crystal films (with packing) behaves 241.6cd/m2 for luminous intensity, 4.173cd/A for lightening efficiency (ηL) and 0.936 lm/W for lightening power (ηP) where voltage of 14V and current (I) of 5.7891mA, which shows that the latter perform is well.